Training load monitoring in elite English soccer: A comparison of practices and perceptions between coaches and practitioners - Weston, W. (Science and Medicine in Football, 2018)
Purpose: To survey practices and perceptions of training load monitoring among soccer coaches and practitioners. Methods: A questionnaire assessed factors influencing training planning, training load practices, and training load feedback and usefulness. The questionnaire was distributed via email and as an online version (Bristol Online Survey Tool) to relevant staff working within elite English Soccer. Results: Respondents represented two groups; those involved with player tactical (coach, n = 94) or physical (practitioner, n = 88) preparation. Coaches worked predominantly with younger players at lower standing clubs while practitioners worked with older players at higher standard clubs. With exception for the influence of current match schedule in training planning, there was coach-practitioner agreement for all training planning questions. There was agreement on some purposes for training load monitoring (maximise fitness, evaluate training) but not others (enhance fitness, reduce injury). For load monitoring methods, the greatest proportion of coach answers was for coach perception (22%); whereas the greatest proportion of practitioner responses was for GPS (22%). Largely, load reports were perceived positively and 84.1% of respondents felt training load monitoring was beneficial to their club. Conclusion: This survey shows coaches and practitioners perceive training load monitoring as worthwhile, with differences in practices and perceptions likely reflecting club infrastructure.